Sistem Informasi Pengelolaan Produksi Tutup dan Botol Pada PT Galenium Pharmasia Laboratories (Studi Kasus: Divisi Plastic Packaging Production) - Sujana, Sujana (TIN: Terapan Informatika Nusantara, 2020)
PT. Galenium Pharmasia Laboratories is a private company engaged in the pharmaceutical sector in Indonesia. The Plastic Packaging Production Division is a relatively new pioneer by PT. Galenium Pharmasia Laboratories with the aim of fulfilling the need for plastic packaging used for packaging materials produced in the existing division in the company. Production management of caps and bottles that are produced is still manual, because in recording production reports, and records of material use do not use the system, it is feared that data management will take time in recording production results, data is also vulnerable to loss and damage so it is feared that information is not conveyed to the production manager . By using information systems based on computer technology, it is expected that material stocks and product stocks can be controlled properly, by making the input process of production data management that is connected to each other between users or employees with the aim of getting information quickly and getting quick responses also between users or employees. The research method uses the Waterfall method, system development uses the Unified Modeling Language, the UML diagram used in this system uses case diagrams, class diagrams, activity diagrams, sequence diagrams. This system is able to manage the production process more closely, from production planning to production completion